Comparative cardiovascular outcomes and safety of hypoglycemic drug classes in patients with type 2 diabetes and hypertension: a multicenter cohort analysis - Zhiyuan Wei; Wanqian Xu; Yu Wang; Yu Tian; Zhongmin Wang; Shenqi Jing; Weina Liu; Sipeng Shen; Chenlong Qin; Xin Zhang; Jingsong Li; Yun Liu (Cardiovascular Diabetology)
Abstract Background Patients with type 2 diabetes (T2D) and hypertension are at increased risk of adverse cardiovascular (CV) events. However, real-world evidence comparing the CV effectiveness and safety of major hypoglycemic drug classes remains limited in this population. This multicenter pooled analysis aims to directly compare the CV outcomes and safety profiles of these key agents in patients with T2D and hypertension. Methods We analyzed electronic health records from two databases in a cohort study of T2D patients with hypertension who had initiated metformin as first-line therapy. Propensity score matching (PSM) and Cox proportional hazards models were used to compare the risks of 3-/4-point major adverse cardiovascular events (MACE) and safety outcomes across drug classes added to metformin: insulin, sulfonylureas (SUs), glucagon-like peptide-1 receptor agonists (GLP-1 RAs), dipeptidyl peptidase-4 inhibitors (DPP4is), glinides, acarbose, and sodium-glucose transporter 2 inhibitors (SGLT2is). Results Compared with insulin, GLP-1 RAs, DPP4is, and glinides were associated with a lower risk of 3-point MACE (HR: 0.48 [0.31–0.76], 0.70 [0.57–0.85], and 0.70 [0.52–0.94], respectively). SUs were associated with a higher risk of 3-point MACE compared with DPP4is (HR: 1.30 [1.06–1.59]). DPP4is, GLP-1 RAs, and glinides showed a lower risk of 3-point MACE compared with acarbose (HR: 0.62 [0.51–0.76], 0.47 [0.29–0.75], and 0.59 [0.43–0.81], respectively). Similar patterns were observed for 4-point MACE. For safety outcomes, DPP4is were associated with a reduced risk of chronic kidney disease, while insulin use was associated with reduced risks of inflammatory polyarthritis and insomnia. However, DPP4is were associated with higher risks of coronary atherosclerotic diseases and hypertensive heart disease. Conclusions This study highlights the differential cardiovascular effectiveness and safety profiles of hypoglycemic therapies in real-world settings, providing valuable insights for optimizing T2D management, particularly in patients with comorbid hypertension.